2010
DOI: 10.5039/agraria.v5i4a631
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos sociais, higiênico-sanitários e reprodutivos da ovinocultura de corte do Estado de Alagoas, Brasil

Abstract: Aspectos sociais, higiênico-sanitários e reprodutivos da ovinocultura de corte do Estado de Alagoas, Brasil RESUMO Objetivou-se com este trabalho realizar um diagnóstico da ovinocultura de corte no Estado de Alagoas por meio do estudo do perfil social, higiênico-sanitário e reprodutivo. Foram analisadas 26 propriedades destinadas à criação de ovinos, distribuídas em 23 municípios nas três Mesorregiões do Estado de Alagoas. Foram aplicados questionários abordando dados sobre o proprietário, a propriedade, o reb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
2
0
8
Order By: Relevance
“…In the State of Sergipe, it was observed that the number of animals per property, in the vast majority of cases, was considered small, with up to 50 heads (46.3% and 24.0%) or varying between 50 and 100 animals (34.2 % and 25.0%), in goat and sheep herds, respectively (Table 1). The results corroborate with other regions of the Northeast, such as in the municipality of Sumé, region of Western Cariri in the state of Paraíba, where 49/60 (81.6%) of goat milk producers had herds with up to 50 heads (SILVA et al, 2013), and in 26 properties intended for sheep breeding in the State of Alagoas, where 38.46% of the farmers had 50 animals on the property, while 26.92% reported that they had between 50 and 100 heads (PINHEIRO JÚNIOR et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the State of Sergipe, it was observed that the number of animals per property, in the vast majority of cases, was considered small, with up to 50 heads (46.3% and 24.0%) or varying between 50 and 100 animals (34.2 % and 25.0%), in goat and sheep herds, respectively (Table 1). The results corroborate with other regions of the Northeast, such as in the municipality of Sumé, region of Western Cariri in the state of Paraíba, where 49/60 (81.6%) of goat milk producers had herds with up to 50 heads (SILVA et al, 2013), and in 26 properties intended for sheep breeding in the State of Alagoas, where 38.46% of the farmers had 50 animals on the property, while 26.92% reported that they had between 50 and 100 heads (PINHEIRO JÚNIOR et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In 36.6% (15) and 45% (25) of goat and sheep farms, respectively, the feces collected from the fold after cleaning are kept in manure pits and out of direct reach of the animals. This percentage can still be considered small, as the accumulation of feces in inappropriate places favors the maintenance of the cycle of gastrointestinal parasites and the proliferation of flies in the environment (ALMEIDA et al, 2010;PINHEIRO JÚNIOR et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Os resultados encontrados nessa pesquisa estão de acordo com o encontrado por Binns et al, (2002), Gouveia et al, (2009, Pinheiro júnior et al, (2010), Silva et al (2011), Coelho et al, (2011 onde afirmam que é muito comum encontrar instalações inadequadas para os animais, onde não há separação por faixa etária e ainda menos para o isolamento de animais doentes afim de evitar a contaminação dos animais sadios. Essas práticas favorecem a disseminação de agentes infecciosos aumentando a taxa de mortalidade entre o rebanho.…”
Section: Algodão Deunclassified
“…No estado do Maranhão também há predominância do sistema de criação extensivo, com baixa utilização de tecnologia, sem estratégias adequadas de sanidade dos animais e não utilização de práticas biotecnológicas na produção e reprodução, ocasionando baixo índice zootécnico. Apesar de apresentar produtividade muitas vezes insatisfatória, esta atividade reveste-se de grande importância cultural, social e econômica, desempenhando um importante papel no desenvolvimento regional, constituindo fonte de renda e de segurança alimentar para populações com elevado risco de exclusão social (PINHEIRO JÚNIOR et al, 2010;FARIAS et al, 2014).…”
Section: Introductionunclassified